Arab Republic of Egypt : Technical Assistance Report-Improving Surveillance of Public-Private Partnerships. (IMF Staff Country Reports; Country Report ;, 2022)
This report summarizes key findings and recommendations of two off-site visits made by Mr. Benoit Wiest, Public Financial Management Advisor at METAC, and Ms. Katja Funke, Expert, between December 2020 and April 2021. The mission worked with the Public-Private Partnerships (PPPs) unit to develop capacities and transparency of fiscal risk management, and support the update of the regulatory framework, as well as the analysis of fiscal risks from PPPs.